2015
DOI: 10.15420/ecr.2015.10.2.118
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Cardiac Death Risk Stratification — An Update

Abstract: Sudden cardiac death (SCD) remains a major public health problem worldwide, yet current methods to identify those at greatest risk are inadequate. High-risk individuals may benefit from potentially life-saving treatment, such as insertion of an implantable-cardioverter defibrillator (ICD). However, such treatments are expensive and have their own associated risks. Furthermore, most cases of SCD occur in the general adult population who may be relatively asymptomatic but yet have an underlying predisposition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Previous studies reported that several ECG features (e.g., heart rate variability, T-wave alternance, early repolarization, late potential, and atrial fibrillation) are associated with SCD and can provide independent values beyond LV dysfunction. 26,27 In fact, the Grad-CAM showed that our neural network model looked at the QRS wave and T wave, which seemed to focus on early repolarization, late potential, and T-wave alternance. Our ECG-based AI algorithm likely integrates specific features associated with SCD and can be accurately applied to a broader spectrum of patients with HF than classical predictive models.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that several ECG features (e.g., heart rate variability, T-wave alternance, early repolarization, late potential, and atrial fibrillation) are associated with SCD and can provide independent values beyond LV dysfunction. 26,27 In fact, the Grad-CAM showed that our neural network model looked at the QRS wave and T wave, which seemed to focus on early repolarization, late potential, and T-wave alternance. Our ECG-based AI algorithm likely integrates specific features associated with SCD and can be accurately applied to a broader spectrum of patients with HF than classical predictive models.…”
Section: Discussionmentioning
confidence: 99%
“…CVD and sudden cardiac deaths rank among the leading causes of morbidity and mortality worldwide and are therefore acknowledged as major healthcare problems [ 7 , 8 ]. The identification of early stages and the knowledge about risk factors is of tremendous importance for the prevention and prophylaxis of this condition [ 9 , 10 ]. Early lifestyle modifications and pharmacological therapies can reduce the progression of CVD with its potentially deleterious consequences.…”
Section: Introductionmentioning
confidence: 99%